Prevalência da deficiência da glicose-6-fosfato desidrogenase em recém-nascidos do estado de Sergipe - Oliveira, Djane Araújo (2017)
Deficiency of glucose-6-phosphate dehydrogenase (G6PD) is a hereditary recessive disease associated with X-chromosome, in which carriers of this deficiency can develop hemolytic anemia during oxidative stress induced by food, medicines and infections. The prevalence of this deficiency is not fully established in the country. In the state of Sergipe, this study aimed to establish this prevalence, through analyzes of blood samples collected on filter paper, of newborns (NB) attended by the State Neonatal Screening Program. The results obtained are presented in the form of two scientific articles (chapter 1 and chapter 2). The first article aimed to identify interferences in the quantitative technique for the diagnosis of G6PD deficiency in samples collected on filter paper of newborns collected from May to October of 2016 at health posts in the state of Sergipe. Divided into five groups, the samples were analyzed under preanalytical and analytical conditions, evaluating the frequency of positive results before and after standardization of the technique. The main interferences observed in the preanalytical phase were the quality of the sample, the time between collection and examination and the temperature during transportation. In the analytical phase the interference in the elution of the samples was observed. The second scientific article refers to the detection of the prevalence of G6PD deficiency in samples of newborns from the state of Sergipe (Chapter 2). Blood samples of newborns collected on filter paper from health posts throughout the state were analyzed between August 2016 and January 2017. In part of the positive samples, the G6PD dosage repetition and complementary tests were performed to evaluate anemia: blood count, reticulocyte count and bilirubin dosage. Confirmed cases were called for clinical evaluation and genetic counseling. Of the 9,040 initial samples, 3,274 were excluded due to poor quality, leaving 5,766 valid samples remaining. The prevalence of G6PD deficiency found in the state of Sergipe was 9.35%, 3.33% female and 4.87% male, with the highest prevalence in the Sergipe State (6.40%). Only 39.99% of the samples followed the Ministry of Health's recommendation for collection between 3 and 7 days after birth. The use of antibiotics that can trigger hemolytic reactions were reported in only 0.35% of the female NBs and 0.64% of the male sex. Of the 473 positive results, 100 newborns were summoned, of whom 50 attended with the parents. Of these, 20 NB presented confirmation of the positive tests, as well as 4 mothers and one father. Four NB presented reduced results for red blood cells, hemoglobin and hematocrit, and two patients presented bilirubin dosage above the reference value. Patients who had the deficiency of the confirmed enzyme participated in a clinical evaluation and genetic counseling, to elucidate the disease, prophylaxis and care with food and use of medicines that can trigger a hemolytic crisis. With this study, it can be concluded that the prevalence of G6PD deficiency in the state of Sergipe is 9.35%, considered high, but consistent with the world literature, mainly due to the influence of African peoples. Likewise, the highest prevalence was in the male sex, and the boys were homozygous that manifested the deficiency associated with the mutation in the G6PD gene.